Investigation of intestinal parasites and ectoparasites in three primary school students in Elazi? - Yilmaz, Mustafa; Korkmaz, Ebru; Karakoç, Selahattin; Yaztürk, Sahin; Kizirgil, Ahmet; Yakupo?ullari, Yusuf (My University, 2007)
The aim of this study was to investigate the prevalence of intestinal parasites and ectoparasites among the students of three primary schools of different socioeconomic levels in Elazi?. At first, a total of 448 students who attend different schools were examined for ectoparasites and then stool and cellophane tapes were collected. Intestinal parasites were found in 119 (26%) of the specimens. The most common parasite was Enterobius vermicularis (8%), followed by Entamoeba coli (8%), Ascaris species and Trichuris species (3%). No scabies were detected in the students, and 23 (5%) of the students had lice.
Elazi?'daki üç ilkö?retim okulu ö?rencilerinde ektoparazit ve ba?irsak paraziti yayginli?inin araştirilmasi.
Keywords: Anal Canal; Animals; Child; Ectoparasitic Infestations; Feces; Humans; Intestinal Diseases, Parasitic; Prevalence; Schools; Socioeconomic Factors; Turkey; anal canal; animal; article; child; feces; human; infestation; intestine infection; parasitology; prevalence; school; socioeconomics; Turkey (republic)